Pengaruh Ukuran Perusahaan, Komite Audit dan Gender Komite Audit Terhadap Audit Report Lag - Sartika, Dewi; Cheisviyanny, Charoline (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to analyze 1) The effect of company size on audit report lag 2) The effect of audit committee on audit report lag 3) The effect of audit committee gender on audit report lag. The novelty of this research from the previous one is that the author uses the audit committee gender variable, where this variable has not been widely researched. This study uses quantitative methods with data sources from company financial report with a sample of 117company in sector property, real estate dan building construction. The analytical method used in this research is descriptive analysis, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple regression analysis, determinant coefficient test, simultaneous test (F) and partial test (T). The results of the study found 1) Company size does not have a negative effect on audit report lag, 2) The audit committee has a negative effect on audit report lag, 3)Gender of the audit committee has no negative effect on audit report lag.